THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN OPTIMIZING DATA RESOURCES THROUGH CLOUD COMPUTING TECHNOLOGY - Naira Azzahra; Ulya Najla Salsabila; Rayyan Firdaus (RADJA PUBLIKA, 2025)
The rapid advancement of information and communication technology has fundamentally transformed how organizations manage their data resources. In today's digital era, data is no longer considered a mere supporting element but a strategic asset that determines organizational competitiveness and sustainability. Management Information Systems (MIS), when integrated with cloud computing technology, offers a modern solution to optimize data collection, storage, processing, and analysis in real-time. This study aims to examine the role of MIS in optimizing data resources through a qualitative literature review approach. The findings indicate that cloud-based MIS enhances operational efficiency, reduces infrastructure costs, facilitates cross-functional collaboration, and strengthens data-driven decision-making. Moreover, this integration supports small and medium enterprises (SMEs) and government institutions by providing affordable and scalable systems. Nevertheless, issues related to data privacy, cybersecurity, and regulatory compliance remain critical challenges that must be addressed through strict data protection policies. This study recommends that organizations develop a cloud-based digital transformation strategy aligned with long-term MIS planning. Further research is suggested to empirically evaluate the effectiveness of cloud-based MIS implementation across various industrial sectors